Strategi Pembelajaran Berdiferensiasi Pada SMP Negeri Se-Kecamatan Pubian - Sulistiyorini; Juhri; M Badrun (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the implementation of differentiated instruction strategies at public junior high schools in Pubian District, Central Lampung. Using a qualitative case study approach, data were collected through classroom observations, in-depth interviews with teachers and principals, and analysis of teaching documents. The findings reveal that the implementation of differentiated instruction remains suboptimal in four key aspects: content, process, product, and learning environment. Most teachers have not conducted diagnostic assessments, resulting in uniform content delivery regardless of students’ readiness levels. The teaching process is still dominated by lecture-based methods with limited learning style adaptation. Although task variations exist, students are not given the freedom to choose products that match their interests and strengths. Moreover, the classroom environment is not fully inclusive, as teachers tend to focus more on high-achieving students. These results highlight the need for systemic support, teacher training, and policy reinforcement to promote inclusive, student-centered learning aligned with the goals of the Merdeka Curriculum.